2016
DOI: 10.1016/j.energy.2016.02.036
|View full text |Cite
|
Sign up to set email alerts
|

The role of monetary transmission channels in transmitting oil price shocks to prices in ASEAN-4 countries during pre- and post-global financial crisis

Abstract: This paper examines the vulnerability of domestic prices against oil price shocks by considering the direct and indirect effects of oil price on consumer price index, which occur through the known channels of the monetary transmission mechanism. We consider interest rate, exchange rate, domestic credit, and share price during the periods before and after the global crisis of 2007-2009 in the ASEAN-4 (Association of Southeast Asian Nations-Indonesia, Malaysia, the Philippines and Thailand) countries. Using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 51 publications
1
29
2
Order By: Relevance
“…The primary aim of monetary policy is to stabilize consumer prices and further improve GDP growth; thus, the changing role of oil price with monetary policy in China could provide evidence for monitoring oil shocks at the macroeconomic level. In this vein, the evidence confirmed that monetary policy may be an accurate tool for capturing the pass-through of oil prices to consumer/producer prices (Razmi et al, 2016;Alvarez and Sanchez, 2019;Wen et al, 2019a). Overall, these results, combined with Figure 2, indicated that the pass-through of oil prices, coupled with a monetary policy, is indeed informative regarding consumer and producer prices.…”
Section: Oil Price Pass-through With a Monetary Policy In Chinasupporting
confidence: 52%
See 3 more Smart Citations
“…The primary aim of monetary policy is to stabilize consumer prices and further improve GDP growth; thus, the changing role of oil price with monetary policy in China could provide evidence for monitoring oil shocks at the macroeconomic level. In this vein, the evidence confirmed that monetary policy may be an accurate tool for capturing the pass-through of oil prices to consumer/producer prices (Razmi et al, 2016;Alvarez and Sanchez, 2019;Wen et al, 2019a). Overall, these results, combined with Figure 2, indicated that the pass-through of oil prices, coupled with a monetary policy, is indeed informative regarding consumer and producer prices.…”
Section: Oil Price Pass-through With a Monetary Policy In Chinasupporting
confidence: 52%
“…First, we provide evidence for the mediating effect of financial markets, then we document the effect of the government debt channel on the oil price-consumer/producer price mechanism. Given the significant changes that have occurred in the financial and oil markets in last two decades, it was desirable to analyze the existence of a channel mechanism in the links between oil price movements and consumer/produce price levels (Alvarez et al, 2011;Razmi et al, 2016;Sek, 2019). To do this, this study used a causal steps approach to explore the mediating effect (Li et al, 2019c).…”
Section: Causal Steps Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Applying two simulation methods [Sims and Zha (1996); Bernanke, et al (2004); Nusair (2016); Razmi, et al (2016)], we find that a contractionary monetary policy resulting from the oil price shocks contributes to an output loss in Pakistan. Figure 1 elaborates a negative relationship between the oil price shocks and the tight monetary policy response pursued by the central bank of Pakistan.…”
Section: Introductionmentioning
confidence: 99%